Pengaruh permainan tradisional kopral terhadap konsentrasi siswa sekolah dasar - M. Alfin Huda; Benny Widya Priadana; Hasan Saifuddin (Physical Education Departement of University PGRI Jombang, 2026)
Concentration is a vital element in achieving academic achievement, especially for elementary school students who are experiencing cognitive development. Concentration problems cause students to struggle to grasp the information, which affects their academic performance overall. This study aims to determine whether traditional corporal games help primary school pupils become more adept at focusing. The research methodology was applied with a quantitative approach through a one-group pretest-posttest design. The research sample utilizes the total number of grade VI students of SD Negeri Gayam 1 as many as 20 students. Data testing was carried out using the Concentration Grid Exercise test. Data interpretation was carried out using the Shapiro-Wilk normality test and paired sample t-test using SPSS software version 30. The study's findings showed an increase in the average concentration score from 4.25 to 6.75 after 12 meeting sessions, an increase of 58.82%. The results of the t-test showed a significant difference after treatment, with a Sig. (2-tailed) value of < 0.001. Thus, the traditional game of Corporal has a positive impact in helping students concentrate more. The small number of samples is the main limitation in the research carried out and the relatively short treatment, so the ability of these findings to be applied widely is still limited. Therefore, the research after that is directed to apply with a larger number of samples, extend the duration of treatment, and combine traditional games with other active learning methods to obtain more comprehensive results.